A Noval Method for Surgical Removal of the Impacted Mandibular Third Molar: Sartawi Technique - Hassan Sartawi (Case Reports in Dentistry)
Background. The goal of this article is to present and evaluate the clinical effectiveness of a new surgical approach using a triangular flap with slight modification and a 3-0 black braided silk surgical suture as flap retractor which is later used after the surgical procedure as a normal suture, aiming to decrease procedure time, soft tissue retraction, and tools for removal of impacted mandibular third molar. Methods. Patients requiring removal of fully impacted or semi-impacted lower third molars are treated with a new approach using minimal steps and tools, a simple triangular flap, slight mucoperiosteum elevation, as the flap sides are secured and reflected with a silk suture by an assistant holding both sides of the suture from behind the patient. Results. The surgical area at the procedure was efficiently exposed, and the separation of the crown from the roots was easily done using a surgical handpiece, separation and removal of the crown, removal of the roots with a straight elevator, without the need of flap retractor or overexposure of the surgical side with a conventional triangular flap or others. After the treatment, the two sides of suture are tied together with double overhand knots, and the surgical site was fully repositioned and closed without any complications. 5- and 7-day follow-up was done on the patients, and no complications were reported. Conclusions. This preliminary study presents a new surgical approach (Sartawi technique) which can be used during extraction of impacted and semi-impacted lower third molars, the results showed that the operation time was noticeably reduced, the size of exposed mucoperiosteum tissue was minimized compared to the conventional method, the use of the mucoperiosteum elevator was eliminated, and number of suture knots and suture used to close the surgical site reduced to a single stitch.